Postoperative venous thromboembolism risk in patients with vulvar carcinoma: An analysis of the National surgical Quality Improvement Program (NSQIP) database - Quinn Kistenfeger; Ashley S. Felix; Caitlin E. Meade; Vincent Wagner; Kristin Bixel; Laura M. Chambers (Elsevier, 2024)
Objectives: Due to low incidence of vulvar cancer (VC), incidence and predictors for development of venous thromboembolism (VTE) are poorly understood. We examined incidence and risk factors associated with VTE in patients undergoing surgery for VC. Methods: We included patients who underwent surgery for VC from the National Surgical Quality Improvement Program database. VTE within the 30-day postoperative period was captured with Current Procedural Terminology codes. Baseline demographics and clinical characteristics were compared between patients with and without VTE. Univariable and multivariable-adjusted exact logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for associations between risk factors and VTE. Results: We identified 1414 patients undergoing procedures for VC from the NSQIP database. Overall, 11 (0.8 %) patients developed VTE. Univariable predictors of VTE included surgery type [compared with simple vulvectomy: radical vulvectomy only (OR = 7.97, 95 % CI = 1.44, infinity) and radical vulvectomy plus unilateral IFN (OR = 15.98, 95 % CI = 2.70, infinity)], unplanned readmission (OR = 11.56, 95 % CI = 2.74, 46.38), deep surgical site infection (OR = 16.05, 95 % CI = 1.59-85.50), and preoperative thrombocytosis (OR = 6.53, 95 % CI = 0.00, 34.86). In a multivariable-adjusted model, longer operative time (≥72 min OR = 11.33, 95 % CI = 1.58-499.03) and preoperative functional status [compared with complete independence: total dependence (OR = 53.88, 95 % CI = 0.85, infinity) and partial dependence (OR = 53.88, 95 % CI = 0.85, infinity)] were associated with VTE. Conclusion: In this cohort of patients with VC undergoing radical vulvectomy, VTE incidence was low. Surgery type, longer operative time, dependent functional status, and wound disruption were identified as risk factors. Our findings highlight opportunities for prophylactic intervention in certain patients.